A case study to validate feasibility of risk proposal in the deployment process of software systems - Ortiz, Felipe
Deployment is the process by which a software system is transferred to a business client. A risk is defined as the likelihood for a loss to occur. In a software project, a risk might imply decreased quality of the software product, increased costs, a delay in project completion or a flaw, among others. A case study is developed with the aim to refine the set of risks. Furthermore, procedures are proposed for their prevention, mitigation and/or transfer for the software system deployment process. This article presents the results of a case study which analyzed the documentation related to deployment of functionalities in a bank’s Human Resources Portal conducted by an Argentina based software Small and Medium Enterprise